Relationship between overnight policy rate, overnight interbank rate, overnight islamic interbank rate.error correction models and granger causality study / Abdul Razak Jambari, Suhana Mohamed and Mohd Azim Sardan - Jambari, Abdul Razak; Mohamed, Suhana; Sardan, Mohd Azim (2012)
In managing monetary policy Bank Negara Malaysia (BNM) has to use the Overnight Policy Rate (OPR), which was introduced in 2004. Changes in the OPR rate will cause a chain of events that affect other interest rates available in the market such as short term interest rate, long term interest rate, short term profit rate and long term profit rate to change .One of the key success factor in managing monetary policy is the ability to understand the relationship between operational targets and ultimate target. Monetary operation of BNM will target the overnight interbank rate (OICR). Liquidity management will target at ensuring the appropriate level of liquidity that would influence the OICR to move close to the OPR. The aims of the paper are to examine the interaction between OPR and OICR in the existence of Islamic variable known as Overnight Islamic Interbank Rate (OIIR). Unit root, co integration and error correction modelling has been applied on the data set to find the short-run and long run relationship between OPR and the interest rates/profit rate. It has been found that there is great amount of heterogeneity in the pass-through among various interest rate/profit rates. This difference is found both in terms of degree and speed of adjustment.